Proceedings of the 2nd International Conference on Robotics, Computer Vision and Intelligent Systems 2021
DOI: 10.5220/0010689900003061
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Detection of 2D Tool Landmarks with Synthetic Training Data

Abstract: In this paper a deep learning architecture is presented that can, in real time, detect the 2D locations of certain landmarks of physical tools, such as a hammer or screwdriver. To avoid the labor of manual labeling, the network is trained on synthetically generated data. Training computer vision models on computer generated images, while still achieving good accuracy on real images, is a challenge due to the difference in domain. The proposed method uses an advanced rendering method in combination with transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This shows that the CAD2Render toolkit is able to create synthetic images that are suitable for this problem space and that images produced by the faster hybrid rendering mode can produce good models as well. Additionally, research has shown that models trained on images generated by CAD2Render perform better on this task than models trained on images generated by simple 2D image augmentations [31]. This shows the benefit of using 3D information to generate training data.…”
Section: Validation Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…This shows that the CAD2Render toolkit is able to create synthetic images that are suitable for this problem space and that images produced by the faster hybrid rendering mode can produce good models as well. Additionally, research has shown that models trained on images generated by CAD2Render perform better on this task than models trained on images generated by simple 2D image augmentations [31]. This shows the benefit of using 3D information to generate training data.…”
Section: Validation Resultsmentioning
confidence: 97%
“…For some applications a large number of images might be needed. Complementary research has experimented with the amount of CAD2Render images needed to train object detection models and has shown that a large amount of images are beneficial when no domain knowledge is used [20]. hybrid renderer regularly fails to show all reflections, shadows and highlights that would be present in images generated with the path tracer.…”
Section: Rendering Profiles and Gpu Accelerationmentioning
confidence: 99%
See 2 more Smart Citations
“…The high fidelity of our synthetic images, their close correspondence with their realworld counterparts, and the controlled variations in the data generation process will be valuable for sim-to-real research. Recently, our dataset was used to train object detection models with synthetic data [33]. The authors trained a model on various sub-sets of our synthetic data to determine which variations improved model performance.…”
Section: Usagementioning
confidence: 99%